Reactive oxygen species prevent imiquimod-induced psoriatic dermatitis through enhancing regulatory T cell function. - Hyung-Ran Kim; Anbok Lee; Eun-Jeong Choi; Min-Pyo Hong; Jeong-Hae Kie; Woosung Lim; Hyeon Kook Lee; Byung-In Moon; Ju-Young Seoh (PLoS ONE, 2014)
Psoriasis is a chronic inflammatory skin disease resulting from immune dysregulation. Regulatory T cells (Tregs) are important in the prevention of psoriasis. Traditionally, reactive oxygen species (ROS) are known to be implicated in the progression of inflammatory diseases, including psoriasis, but many recent studies suggested the protective role of ROS in immune-mediated diseases. In particular, severe cases of psoriasis vulgaris have been reported to be successfully treated by hyperbaric oxygen therapy (HBOT), which raises tissue level of ROS. Also it was reported that Treg function was closely associated with ROS level. However, it has been only investigated in lowered levels of ROS so far. Thus, in this study, to clarify the relationship between ROS level and Treg function, as well as their role in the pathogenesis of psoriasis, we investigated imiquimod-induced psoriatic dermatitis (PD) in association with Treg function both in elevated and lowered levels of ROS by using knockout mice, such as glutathione peroxidase-1(-/-) and neutrophil cytosolic factor-1(-/-) mice, as well as by using HBOT or chemicals, such as 2,3-dimethoxy-1,4-naphthoquinone and N-acetylcysteine. The results consistently showed Tregs were hyperfunctional in elevated levels of ROS, whereas hypofunctional in lowered levels of ROS. In addition, imiquimod-induced PD was attenuated in elevated levels of ROS, whereas aggravated in lowered levels of ROS. For the molecular mechanism that may link ROS level and Treg function, we investigated the expression of an immunoregulatory enzyme, indoleamine 2,3-dioxygenase (IDO) which is induced by ROS, in PD lesions. Taken together, it was implied that appropriately elevated levels of ROS might prevent psoriasis through enhancing IDO expression and Treg function.